OP0259 OVERWEIGHT AND OBESITY IN PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS ENROLLED IN THE GERMAN NATIONAL PAEDIATRIC RHEUMATOLOGIC DATABASE (NPRD). (June 2019) - Milatz, Florian; Klotsche, Jens; Niewerth, Martina; Geisemeyer, Nils; Hörstermann, Jana; Ganser, Gerd; Foeldvari, Ivan; Thon, Angelika; Berendes, Rainer; Hufnagel, Markus; Hospach, Toni; Minden, Kirsten
Abstract : Background: Patients with juvenile idiopathic arthritis (JIA) may have a different body composition associated with reduced muscle mass and increased fat mass [1]. They display decreased physical fitness, perform less strenuous physical activities, and spend more time sleeping than do healthy children. A lower level of physical activity is associated with deconditioning and functional deterioration, favoring an inactive lifestyle. The risk of overweight might be further increased by the glucocorticoid treatment. Objectives: Since obesity can increase inflammatory processes, cause early atherosclerotic changes and promote metabolic disorders, the objectives were a) to determine the prevalence of overweight and obesity in children and adolescents with JIA, and b) to examine the association between overweight and health-related parameters in this population. Methods: A cross-sectional analysis of physicians' recorded body weights and heights of patients with JIA enrolled in the NPRD in the year 2016 was performed. Overweight was defined as BMI >90th sex- and age-specific percentile and obesity as BMI >97th percentile. For comparison with data from the general German population [2], patients aged 3 to 17 years were considered. A linear regression model was used to explore the association between overweight and both clinical as well as self-reported outcomes. Results: In total, data from 6.860 children and adolescents with JIA (age 11.5 ± 4 years, disease duration 4.6 ± 3.6 years, 67% girls, 39% persistent oligoarthritis) were analyzed. Overweight was found in 14% (including 6% obesity) of JIA cases. Comparative data from the German general population report an overweight prevalence of 15% (including 6% obesity). In contrast to the general population, overweight rates in JIA differed between girls and boys (girls 14% vs. boys 16%, p<0.05). Patients with psoriatic arthritis (20%) and systemic JIA (18%) showed the highest overweight rates. In multivariate analyses, age (OR 1.06; 95%CI: 1.04-1.09), male sex (OR 1.21; 95%CI: 1.01-1.44), functional limitations (OR 1.29; 95%CI: 1.04-1.59), as well as therapy with biological DMARDs (OR 1.48; 95%CI: 1.22-1.80) and systemic glucocorticoids (OR 1.40; 95%CI: 1.14-1.71) were significantly associated with overweight. Conclusion: The prevalence of overweight and obesity in young patients with JIA is similar to that of children and adolescents in the general population. The overweight rate increases with age and is strongly associated with functional restrictions and treatment with glucocorticoids. The role of overweight in the long-term outcome of JIA is an issue that still needs to be addressed. References: [1] Grönlund MM, et al. Juvenile idiopathic arthritis patients with low inflammatory activity have increased adiposity. Scand J Rheumatol 2014;43:488–92. [2] Schienkiewitz A, et al. Übergewicht und Adipositas im Kindes- und Jugendalter in Deutschland. Journal of Health Monitoring 2018; 3:16–23. Acknowledgement: The National Paediatric Rheumatological Database has been funded by the German Children Arthritis Foundation (Deutsche Kinder-Rheumastiftung), AbbVie, Pfizer and Chugai. Disclosure of Interests: Florian Milatz: None declared, Jens Klotsche: None declared, Martina Niewerth: None declared, Nils Geisemeyer: None declared, Jana Hörstermann: None declared, Gerd Ganser: None declared, Ivan Foeldvari Consultant for: Chugai, Novartis, Angelika Thon: None declared, Rainer Berendes: None declared, Markus Hufnagel: None declared, Toni Hospach Speakers bureau: Chugai, Roche, Novartis, Kirsten Minden Consultant for: AbbVie